Human Resource Management Strategy in Improving Public Service Performance at the Population and Civil Registration Office of Gowa Regency - Nasir, Nasir (Journal Business Inovation, Accounting and Management, 2025)
Quality public services are an indicator of the success of governance, where the strategic role of human resource management (HR) greatly determines service performance. This study aims to analyze HR management strategies in improving public service performance at the Population and Civil Registration Office of Gowa Regency. The research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. The theoretical framework used refers to six HR management indicators according to Dessler, namely HR planning, recruitment and selection, training and development, performance appraisal, compensation, and employment relations. The results of the study show that the HR management strategy in this agency has not been fully integrated strategically. Planning is not competency-based, the recruitment process for non-ASN personnel is less transparent, training is still limited, performance appraisals are administrative, compensation is not performance-based, and employment relations are still hierarchical. In conclusion, the success of improving public services is greatly influenced by an effective HR management strategy, so it is necessary to strengthen all aspects of human resource management in a comprehensive and sustainable manner